Atypical Parkinsonism Revealing a Late Onset, Rigid and Akinetic Form of Huntington's Disease. (28th July 2011) - Ciammola, A.; Sassone, J.; Poletti, B.; Mencacci, N.; Benti, R.; Silani, V.
Abstract : Huntington's disease (HD) is a rare hereditary neurodegenerative disorder characterized in over 90 percent of cases by chorea as the presenting motor symptom. We report a 54-year-old male who presented with Parkinsonism as the initial symptom of the disease. Genetic analysis revealed expansion of 40 CAG repeats, and brain MRI showed both severe caudate nuclei and cortical atrophy. Single-photon emission computed tomography (SPECT) imaging of the dopamine transporter showed nigrostriatal pathway degeneration. Here, we also describe his 2 years of clinical followup after ensuing dopaminergic stimulation.